Critical Appraissal of Challenges and Prospects of Ethiopia’s National Dialogue - Tura, Jara Samuel (European Scientific Journal, ESJ, 2023)
Before the end of 2021, on December 29, the Ethiopian Parliament adopted a law establishing a National Dialogue Commission with the objective of bolstering national consensus and restoring social values in Ethiopia. Since then, a number of other actions have been taken, including the establishment of a list of eleven people to function as commissioners. Despite its establishment by the house of people representative, various stakeholders have expressed their ambitions and worries about the success of the dialogue commission and its impartiality and inclusiveness. A principled national dialogue has been shown to build national consensus on social, political, or economic issues through an open and tolerant exchange of ideas. Such a national dialogue must encompass a broad range of stakeholders in all three phases—preparation, process, and implementation—in order to succeed. However, there are concerning issues that should be considered as a challenge in all three phases, including but not limited to partiality, the active fighting in the region, and exclusionary. The challenges would lead to the aborting of the objectives of the national dialogue unless they were dealt with carefully and with strong regard in all stages of the national dialogue. If it is done carefully, it has the prospects of creating legitimacy for national institutions, and then, afterward, it could pave the way for the smoothing of national dialogue, which has the vision of creating a common future among nations. and acceptance in the process of the national dialogue. This paper has the objective of assessing the prospects and challenges of the Ethiopian national dialogue and to recommend a better approach to counter the undermining factors in the dialogue process. In doing so, it assesses the prospects and challenges of national dialogue from the perspective of other states' experiences in the same milieu. Against this background, the study employs an extended literature review method from the touch stones of Berghof foundation reports on the national dialogue. After a profound assessment of the prospects and challenges of Ethiopian national dialogue, building peace in the war-torn areas of the country, and the willingness and commitment of political parties, are some of the tangible challenges. whereas, creating an inclusive nation-building process, enhancing rule of law, and democratization are the prospects of the national dialogue. The study makes the recommendation that, for a successful national dialogue in Ethiopia, peace building with political parties in the northern part of Ethiopia, a ceasefire agreement with the OLF (aka Shane), consultation with major stakeholders, extending the term limits of the national dialogue commission, establishing ad hoc panel of historians, including major political parties, securing the impartiality of the conveners of the national dialogue, mainly in the process phase, and limiting the involvement of the executive branch from interference in all stages are necessary